Occlusal Contact Changes Before and After Orthodontic Treatment of a Group of Child & Adolescent Patients with TMJ Disturbance - Deng Yumeng; Fu MinKui (Australasian Orthodontic Journal, 1995)
Occlusal contacts were examined before and after orthodontic treatment in 32 eight- to seventeen-years-old patients with temporomandibular joint disturbance. Add-Picture, a computer image system, was applied to a silicone occlusal record obtained in the intercuspal position (ICP) to assess the qualitative and quantitative changes of occlusal contacts. Comparing the two images before and after treatment, significant difference was noted in the number, size, location and type of contacts. After orthodontic treatment: the mean number of contacts on anterior teeth reduced, the mean area per contact decreased, the number of contacts on centric stops increased and type IV contacts (on the inclined plane) decreased. The present study indicates that orthodontic treatment has a positive effect, both qualitatively and quantitively, on the distribution of occlusal contacts in ICP and seems to contribute to the establishment of occlusal stability in ICP.